2013
DOI: 10.1111/jam.12144
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of culture conditions for biomass production of probiotic gut-borneSaccharomyces cerevisiaestrain able to reduce fumonisin B1

Abstract: Aim: To evaluate the ability of probiotic Saccharomyces cerevisiae RC016 strain to reduce fumonisin B 1 (FB 1 ) in vitro and to optimize the culture conditions for the growth of the yeast employing surface response methodology. Methods and Results: Using Plackett-Burman screening designs (PBSD) and central composite designs (CCD), an optimized culture medium containing (g l À1 ) fermentable sugars provided by sugar cane molasses (CMs), yeast extract (YE) and (NH 4 ) 2 HPO 4 (DAP) was formulated. The S. cerevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…In our research, high and diverse activity of the analysed S. cerevisiae strains reducing FUM concentration was also shown, and the results agree with those of Pizzolitto et al (2012b) [56]. Furthermore, Armando et al (2013), who also observed high FB 1 binding properties of S. cerevisiae yeast (strain RC016), observed that ability of binding the mycotoxin increases along with concentration [59]. Our results also showed that the strains isolated from the feed were characterised by a slightly lower ability to remove FUM (67.43% after 24 h of incubation) than achieved by baker's yeast (70.71-74.47% reduction of FUM concentration after 24 h of incubation) or strains isolated from a distillery environment (72.88% and 73.04% reduction of mycotoxin concentration after 24 h of incubation).…”
Section: Discussionsupporting
confidence: 92%
“…In our research, high and diverse activity of the analysed S. cerevisiae strains reducing FUM concentration was also shown, and the results agree with those of Pizzolitto et al (2012b) [56]. Furthermore, Armando et al (2013), who also observed high FB 1 binding properties of S. cerevisiae yeast (strain RC016), observed that ability of binding the mycotoxin increases along with concentration [59]. Our results also showed that the strains isolated from the feed were characterised by a slightly lower ability to remove FUM (67.43% after 24 h of incubation) than achieved by baker's yeast (70.71-74.47% reduction of FUM concentration after 24 h of incubation) or strains isolated from a distillery environment (72.88% and 73.04% reduction of mycotoxin concentration after 24 h of incubation).…”
Section: Discussionsupporting
confidence: 92%
“…Fumonisin B 1 was successfully removed by a S. cerevisiae strain through physisorption as reported by Pizzolitto et al . Fumonisin‐detoxifying organisms are exploitable in the agriculture and an optimization study for cost‐efficient biomass production by a probiotic S. cerevisiae strain was recently published .…”
Section: Applications Of Yeastsmentioning
confidence: 79%
“…Nitrogen sources are also essential components for the synthesis of microbial cell proteins and nucleic acids and can have an important influence on cell growth and the accumulation of metabolites. [17] The results showed that the strains could utilize both organic and inorganic nitrogen sources for growth and DEX production ( Figure 2B). Among the nitrogen sources tested, casein was found to induce maximum DEX production (38.91 U/mL, P < 0.05) and cell growth (1.378, P < 0.05).…”
Section: Optimization Of Fermentation Conditions For Dextranase Produmentioning
confidence: 99%